1986
DOI: 10.1002/bit.260280506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dissolved carbon dioxide on penicillin fermentations: Mycelial growth and penicillin production

Abstract: The effect of dissolved carbon dioxide on the specific growth rate and the penicillin production rate of Penicillium chrysogenum was examined experimentally. The dissolved carbon dioxide was found to inhibit the specific growth rate and the penicillin production rate when the aerated submerged penicillin fermentation was exposed to influent gases of 12.6 and 20% carbon dioxide, respectively. Upon exposure to influent gases of 3 and 5% carbon dioxide, no pronounced metabolic inhibition was noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Vardar and Lilly (1982) demonstrated that carbon dioxide levels in the exhaust gas of 4.2±4.8% had no impact on the speci®c penicillin production rate compared to control levels of 0.6±0.7%. A number of studies have demonstrated the inhibitory eects of carbon dioxide levels on growth, productivity, and morphology for a [Nash, 1974], Penicillium [Ho et al, 1986]). However, these studies required carbon dioxide levels greater than 5% (in the exhaust gas) before inhibitory eects were observed.…”
Section: Sensitivity To Carbon Dioxidementioning
confidence: 98%
See 1 more Smart Citation
“…Vardar and Lilly (1982) demonstrated that carbon dioxide levels in the exhaust gas of 4.2±4.8% had no impact on the speci®c penicillin production rate compared to control levels of 0.6±0.7%. A number of studies have demonstrated the inhibitory eects of carbon dioxide levels on growth, productivity, and morphology for a [Nash, 1974], Penicillium [Ho et al, 1986]). However, these studies required carbon dioxide levels greater than 5% (in the exhaust gas) before inhibitory eects were observed.…”
Section: Sensitivity To Carbon Dioxidementioning
confidence: 98%
“…High levels of carbon dioxide (7± 10%) in exhaust gas have been associated with fermentations in large vessels (Onken and Liefke, 1989). These levels have shown to be detrimental to the productivity of S. erythraea (Nash, 1974), Aspergillus (McIntyre and McNeil, 1997), and Penicillium (Ho et al, 1986).…”
Section: Introductionmentioning
confidence: 97%
“…Two research groups have reported the effects of dissolved CO 2 in two important industrial strains, Penicillium chrysogenum (Edwards and Ho, 1988;Ho and Smith, 1986) and Aspergillus niger McNeil, 1997a,b,c, 1998). Their morphologies, being of importance in the evaluation of cell growth and product formation, were apparently affected if the influent CO 2 concentration was higher than 5%.…”
Section: Introductionmentioning
confidence: 98%
“…This would result in a CO 2 concentration in culture media much higher than with air supply only. This high CO 2 concentration may inhibit the metabolic activities of microbial cells (Ho and Smith, 1986;McIntyre and McNeil, 1997c).…”
Section: Introductionmentioning
confidence: 98%
“…The morphology changes observed with A. pullulans may be due in part to the high concentration of dissolved carbon dioxide since a similar aggregation phenomenon has been observed with the fungus Penicillium chrysogenum when various concentrations of carbon dioxide at atmospheric pressure were bubbled through the fermentation medium (Smith and Ho 1985;Ho and Smith 1986). The anaesthetic efficiency of a molecule can be related to its olive oil/water partition coefficient (Seeman 1972).…”
Section: Methodsmentioning
confidence: 99%